2022
DOI: 10.3389/fped.2022.840444
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Diaphragmatic Ultrasonography for the Weaning Outcome in Mechanically Ventilated Children Aged 1–3 Years

Abstract: BackgroundThere are estimated 20% of mechanically ventilated patients having difficulty in weaning from the ventilators, and the weaning process accounts for 40% of the whole ventilation time. Reliable tools are urgently needed to estimate the weaning outcome. Diaphragmatic ultrasonography, as a relatively good predictive method for the adults, was measured in this study, assessing the value of each indicator of diaphragmatic ultrasonography to predict the outcomes of ventilator weaning from mechanically venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Amrousy's study had two LUS cut-off points ( 24 ), but Jiang's study had four LUS cut-off points ( 31 ). One study looked at left and right DE ( 25 ), while the other looked at left and right DTF ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amrousy's study had two LUS cut-off points ( 24 ), but Jiang's study had four LUS cut-off points ( 31 ). One study looked at left and right DE ( 25 ), while the other looked at left and right DTF ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the QUADAS-2 tool assessing risk of bias and applicability concerns of the included studies were shown in Figure 2 . The possibility of patient selection bias was mostly related to the fact that four studies included patients who were either eligible for weaning or planned to be weaned rather than patients who were randomly selected ( 21 , 24 , 25 , 29 ). Index test poses a risk since they do not clearly reveal whether the ultrasound was performed without knowledge of the clinical outcomes ( 21 , 23 , 27 , 28 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on diaphragm monitoring has focused on the importance of this muscle in many respiratory disorders: diaphragm thickness and diaphragm thickening fraction (DTF) have been related to the time on invasive mechanical ventilation (IMV) in adults [1,2] and pediatric patients [3], as well as with extubation failure [3][4][5]. Being able to reproduce this nding in premature infants may help to reduce extubation failure in this population [6].…”
Section: Introductionmentioning
confidence: 99%